Joint A4NH/ISPC Workshop on Nutrition: Brief 47 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2015)
This brief highlights the insights and recommendations from a joint A4NH/ISPC workshop on nutrition held in September 2014. The two-day workshop was organized as a follow-up to the 2013 Science Forum on “Nutrition and Health Outcomes: Targets for agricultural research” and was attended by over 40 participants.